Associations between unit workloads and outcomes of first extubation attempts in extremely premature infants below a gestational age of 26 weeks - Mari Oma Ohnstad; Mari Oma Ohnstad; Hans Jørgen Stensvold; Are Hugo Pripp; Are Hugo Pripp; Christine Raaen Tvedt; Lars-Petter Je; Lars-Petter Je; Lars-Petter Je; Henriette Astrup; Beate Horsberg Eriksen; Beate Horsberg Eriksen; et al. (Frontiers Media S.A., 2023)
ObjectiveThe objective was to explore whether high workloads in neonatal intensive care units were associated with short-term respiratory outcomes of extremely premature (EP) infants born <26 weeks of gestational age.MethodsThis was a population-based study using data from the Norwegian Neonatal Network supplemented by data extracted from the medical records of EP infants <26 weeks GA born from 2013 to 2018. To describe the unit workloads, measurements of daily patient volume and unit acuity at each NICU were used. The effect of weekend and summer holiday was also explored.ResultsWe analyzed 316 first planned extubation attempts. There were no associations between unit workloads and the duration of mechanical ventilation until each infant's first extubation or the outcomes of these attempts. Additionally, there were no weekend or summer holiday effects on the outcomes explored. Workloads did not affect the causes of reintubation for infants who failed their first extubation attempt.ConclusionOur finding that there was no association between the organizational factors explored and short-term respiratory outcomes can be interpreted as indicating resilience in Norwegian neonatal intensive care units.